Fostering Millennial Entrepreneurship Students – Issues and Challenges - Noor Azuan Hashim; Farhana Sidek; Shifa Mohd Nor (Indonesian Journal of Business and Entrepreneurship (IJBE), 2022)
Governments worldwide have increasingly recognized their interest in entrepreneurship and have introduced it to various settings, not only among the officials but also schools and Higher Education Institutions (HEI). Many incentives have been given to those who embark on entrepreneurship. The Malaysian government has made all colleges in Malaysia introduce entrepreneurships courses to make students aware of the importance of entrepreneurships. Thus, there are questions were raised on the effectiveness of the entrepreneurship programme in the university. Moreover, and the kinds of improvements that need to be embedded in these programmes. This study is among the first to explore this issue by gathering information from the students majoring in entrepreneurship and who are recently graduated. Both quantitative and qualitative methods have been adopted to get the details of the issues being studied. Thirty-three students were surveyed, and ten respondents were called for semi-structured interviews. Many students stated that they were not ready to become an entrepreneur entrepreneurs because they are were really not confidence confident in doing so, and some said they needed to work to get some money and experience first. Some stated that the programme should be improved by creating an entrepreneurship ecosystem among students and lecturers. This study contributes to entrepreneurship education literature by enhancing understanding of the needs of students during the entrepreneurial learning process. In practice, this study offers raze and valuable insights into how to design and implement designing and implementing an effective HEI entrepreneurship training programme. Keywords: entrepreneurship, entrepreneurship education, effectiveness, higher learning institution, Malaysia